Does Commuter’s Impact on Social and Economic: Daylight Activities In Sukabumi City - Elan Eriswanto; Alhidayatullah (International Journal of Economics (IJEC), 2023)
Commuter or Indonesian "nglaju" is a form of non-permanent mobility that is growing rapidly, especially in big cities in Indonesia. With this commuter, of course, there are several impacts caused, which include population mobility, economic growth, and employment. The purpose of this study is to provide an overview to the Sukabumi City government regarding the social and economic impact of commuter activities in Sukabumi City. This study uses qualitative data analysis techniques, namely data analysis carried out simultaneously with data collection or at the time of observation and interviews, where the population is residents of Sukabumi City and residents outside who are active in Sukabumi City as many as 385,710. The sampling technique uses a web raosoft.com sample size with a data accuracy level of 95% and a margin of error of 5%, then a sample of 384 respondents was obtained. The method of collecting data in this study uses literature studies, observations, and interviews. This commuter has an impact on increasing the number of residents during the day by 33,844 people or 9.6%. And the significant socio-economic impact in Sukabumi City resulted from shopping, culinary, and education activities by 69.5%. This means that 49.3% of commuters who carry out their activities in Sukabumi City have the purpose of shopping and culinary centers. This result, certainly has an impact on economic activities in Sukabumi City, especially the MSME economy, namely the increase in income from MSMEs. This research examines the social and economic impact of commuting and contributes to expanding the literature on commuting and the economics of community activity.